Rembuk Tiuh in Handling Juvenile Crime in Theft Cases - Amalia, Hanisa; Hamsiri (Universitas Islam Negeri Raden Intan Lampung, 2025)
The resolve to the crimes of rubber theft by child perpetrators in Blambangan Umpu Village, Way Kanan Regency through rembuk tiuh is a form of restorative justice in the form of traditional deliberation which provides justice for the victims and perpetrators. This paper to analyze implementation and inhibiting factors of rembuk tiuh are in the resolve the criminal acts of theft with child perpetrators in Blambangan Umpu Village, Way Kanan Regency. The research uses a normative juridical approach and empirical juridical approach by using primary data in the form of interviews and secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials which are analyzed qualitatively. The results of the research and discussion show that the implementation of rembuk tiuh in resolve the criminal acts of theft with child perpetrators can be said to be effective in achieving justice for victims and perpetrators. Compensation fine by the perpetrator to the victim is a restoration to the original condition and are not a form of retaliation. The absence of punishment for child perpetrators gives the opportunity to grow and develop properly. The presence of traditional leaders in the discussion as mediators helps seek a common solutions and agreements. The dominant factors inhibiting the implementation of rembuk tiuh are the lack of role of regional government in encouraging the resolution of criminal acts of theft through rembuk tiuh and communities who do not fully understand rembuk tiuh as a way to resolve criminal acts of theft.